Thermodynamic Properties of 4’-Demethylepipodophyllotoxin in Dimethyl Sulfoxide - Han, Nan (Asian Journal of Chemistry, 2014)
In this study, the enthalpy of dissolution of 4'-demethylepipodophyllotoxin (DMEP) in dimethyl sulfoxide (DMSO) was measured by using a RD496-2000 Calvet Microcalorimeter at 309.65 K under atmospheric pressure. The differential enthalpy (DdifHm) and molar enthalpy (DsolHm) about 4'-demethylepipodophyllotoxin dissolution in dimethyl sulfoxide were determined and the relationship between heat and the amount of solute was established as well. Based on these experimental data and calculated results, the kinetic equation, half-life, DsolHm, DsolGm and DsolSm of the dissolution process were obtained. This study can provide a simple method to determine the half-life of a drug, as well as offer a theoretical reference for the clinical application of 4'-demethylepipodophyllotoxin .